Integrasi Imtaq Dan Iptek Dalam Pengembangan Pendidikan Islam - Heru Setiawan (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2016)
The integration of science and religion has an important value to dispel the assumption between Religion (Islam) is not an old-fashioned religion that does not accept the advance of science and technology, but is open Religion and revelation (al-Qur'an) is the source or inspiration of all sciences. Talking about the integration of imtaq and science and technology as one of the models in the development of Islamic education curriculum. The theory used in this study uses globalization that continues to grow in the midst of people's lives. Based on the study of the theories, the writer can give a little hypothesis about the impact of science and technology advancement that demands the existence of new and innovative models, especially in Islamic education as a form of response and a filter against the negative effects of science and technology, resulting in a model of imtaq and science integration as a model of development of Islamic education curriculum.